Moso bamboo (Phyllostachys edulis (Carrière) J. Houzeau) invasion affects soil microbial communities in adjacent planted forests in the Lijiang River basin, China - Sun, Hongping; Hu, Wenyu; Dai, Yuxin; Ai, Lin; Wu, Min; Hu, Jing; Zuo, Zhen; Li, Mengyao; Yang, Hao; Ma, Jiangming (Frontiers in Microbiology, 2023)
Introduction Moso bamboo (Phyllostachys edulis (Carrière) J. Houz.), the most widely distributed economic bamboo species in southern China, can easily invade adjacent communities due to its clonal reproduction. However, there is little information on the effects of its establishment and expansion to adjacent forest soil communities, particularly in planted forests. Methods We investigated the relationships between soil properties and the microbial community during bamboo invasion under different slope directions (shady or sunny slope) and positions (bottom, middle, or top slope), in three typical stand types (bottom: pure moso bamboo, middle: mixed stands of moso bamboo and Masson pine (Pinus massoniana Lamb.), and top: pure Masson pine) in the Lijiang River Basin. This study aimed to explore the effects of key environmental factors on soil microbial composition, diversity, and abundance. Results and Discussion The results showed that the abundance of Acidobacteria bacterium and Acidobacteria bacterium 13_2_20CM_58_27, and Verrucomicrobia bacterium decreased as the slope increased (p < 0.05), whereas the abundance of Alphaproteobacteria bacterium, Actinobacteria bacterium, Trebonia kvetii, and Bradyrhizobium erythrophlei increased as the slope increased (p < 0.05). However, the difference of slope direction on microbial communities was not significant. The pH, organic matter (OM) and total phosphorus (TP) were the key soil environmental factors; most microorganisms (Betaproteobacteria bacterium, Candidatus Eisenbacteria bacterium, Betaproteobacteria bacterium SCGC_AG − 212 − J23, Gemmatimonadetes bacterium, Actinobacteria bacterium 13_2_20CM_2_66_6, and Myxococcaceae bacterium) showed a positive relationship with pH and a negative relationship with OM and TP. Slope position significantly affected OM, calcium (Ca), total nitrogen (TN), available phosphorus (AP), hydrolyzed nitrogen (HN), pH, and microbial abundance and composition. Slope direction significantly affected TP and magnesium (Mg). The structural equations also indicated that slope position had an effect on microbial composition, abundance, and diversity. Slope position was negatively correlated with pH (r = −0.333, p = 0.034) and positively correlated with OM (r = 0.728, p < 0.001), TN (r = 0.538, p < 0.001) and Ca (r = 0.672, p < 0.001); pH was positively correlated with microbial composition (r = 0.634, p < 0.001), abundance (r = 0.553, p < 0.001) and diversity (r = 0.412, p = 0.002), TN was positively correlated with microbial composition (r = 0.220, p = 0.014) and abundance (r = 0.206, p = 0.013), and Ca was negatively correlated with microbial composition (r = −0.358, p = 0.003) and abundance (r = −0.317, p = 0.003). Slope position can also influence microbial composition (r = 0.452, p < 0.001) directly. In addition, slope direction had an indirect effect on microbial diversity through total potassium (TK). Therefore, we proposed that the different variations in microbial community during bamboo invasion could be related to the influence of invasion on the soil properties at different invasion stages.